Establishment and Study of an Evaluation Model for the Exploitation Effect of University Scientific and Technological Patents - Zhou, Renguo (International Journal of Emerging Technologies in Learning (iJET), 2022)
Due to the lack of sufficient understanding by the public of the process and mechanism of how university patents are exploited, the exploitation effect of university patents is not satisfactory. Therefore, it is necessary to effectively evaluate the exploitation effect of university patents in order to explore a reasonable path for and expand the role of university patent exploitation. Currently, there has been few research on how to evaluate the exploitation effect of university patents. To this end, this paper focuses on university scientific and technological patents and explores the effective evaluation method for the exploitation effect of these patents. First, market share, market benefit, patented technology maturity, enterprise nature and government support were selected as the evaluation indicators for the exploitation effect of the scientific and technological patents in colleges and universities in the study area. It was proposed that the five influencing factors and the exploitation effect of university scientific and technological patents interact with and influence each other. Then a combined model based on grey prediction GM (1,1) model and BP neural network model was constructed for the evaluation of the exploitation effect of scientific and technological patents in colleges and universities, which proved to have better prediction performance. The experimental results proved the effectiveness of the prediction model, and also verified the interactions between the five influencing factors and the exploitation effect of university scientific and technological patents.